Backward design and authentic performance tasks to foster English skills: Perspectives of Hungarian teacher candidates - Carlos L. Alvarez; Branca Mirnic; Jardel C. Santos; Tatiana G. Pineda (Journal of Pedagogical Research, 2024)
This quasi-experimental research aimed to describe the syllabus design process using the backward design model and its features to determine the teacher candidates' perceptions of its application in the English Skills Development course. To achieve these objectives, the syllabus based on the BDM was designed before starting the course; after that, it was applied to sixteen students enrolled in a teacher preparation program at a Hungarian university in Budapest. At the end of the course, the participants developed sixteen final projects related to the main topic of the course, teaching English as a Foreign Language in Hungary and following the Goal, Role, Audience, Situation, Product, Standard (GRASPS) framework to conduct authentic performance tasks. This research method involves collecting data through written reflections, focus-group interviews and content analysis of the conducted performance tasks. The results show that BDM and authentic performance tasks can be used as a coherent, organized, and flexible syllabus design that supports EFL students by providing differentiated instruction to foster their English skills, creativity, problem-solving and critical thinking skills, long life and autonomous learning, and digital competencies. Furthermore, the results of the study make an essential contribution to the context of EFL by suggesting that planning the syllabus based on the BDM creates strong connections between course objectives, assessment, content, teaching strategies, and technology, thereby offering a practical framework for educators to enhance their teaching practices in the digital age.